Collaborative emergency adaptation for ripple effect mitigation in intertwined supply networks - Dmitry Ivanov (Annals of Operations Research, 2023)
For the first time, the ripple effect is examined in the setting of an intertwined supply network. Through simulations, we model the disruption propagation in supply chains having common suppliers. We explore conditions under which a collaborative coordination of re-purposed capacities and shared stocks can help mitigate the ripple effect and improve recovery performance. As a result, we conceptualize the notion of collaborative emergency adaptation contributing to development of "network-of networks" and viability perspective in supply chain resilience management. We illustrate our approach with anyLogistix simulations and deduce some generalized theoretical and managerial insights on how and when a collaborative emergency adaptation can be implemented and help improve supply chain resilience and viability.
Keywords: 000; Supply chain resilience; Ripple effect; Intertwined supply network; Collaboration; Adaptation; Viability; anyLogistix